ISLAMIC PARENTING ANAK USIA DINI DALAM PERSPEKTIF JAMAL ABDURRAHMAN - Nuraini, Suci (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2024)
This study aims to analyse the application of prophetic parenting in early childhood based on the views of Jamal Abdurrahman. The research was conducted through a literature study with a qualitative approach and is descriptive-analytical in nature. Primary data was obtained from the book Islamic Parenting: Child Education The Prophet's Method. The research was conducted by content analysis of Jamal Abdurrahman's work. The results showed that prophetic parenting aims to form children who are devoted to Allah SWT, shalih/shalihah, noble, obedient, responsible, and brave. The material taught includes faith education, morals, worship, and science. The methods used by the Prophet include setting an example, giving advice, getting used to goodness, utilising free time, giving punishment, and instilling motivation. Evaluation is carried out systematically through daily observations, weekly and monthly records with indicators that refer to the target learning material. This research confirms the importance of applying Islamic values in educating children.